Emma Susana Speratti-Piñero, Pasos hallados en "El reino de este mundo". El Colegio de México, México, 1981; 212 pp. - Díaz Ruiz, Ignacio (El Colegio de México, 1983)
Se reseñó el libro: Pasos hallados en "El reino de este mundo".